Keratin 19 as a key molecule in progression of human hepatocellular carcinomas through invasion and angiogenesis. Issue 1 (December 2016) - Takano, Masato; Shimada, Keiji; Fujii, Tomomi; Morita, Kohei; Takeda, Maiko; Nakajima, Yoshiyuki; Nonomura, Akitaka; Konishi, Noboru; Obayashi, Chiho
Abstract Background Keratin (K) 19-positive hepatocellular carcinoma (HCC) is well known to have a higher malignant potential than K19-negative HCC: However, the molecular mechanisms involved in K19-mediated progression of HCC remain unclear. We attempted to clarify whether K19 directly affects cell survival and invasiveness in association with cellular senescence or epithelial-mesenchymal transition (EMT) in K19-positive HCC. Methods K19 expression was analysed in 136 HCC surgical specimens. The relationship of K19 with clinicopathological factors and survival was analysed. Further, the effect of K19 on cell proliferation, invasion, and angiogenesis was examined by silencingK19 in the human HCC cell lines, HepG2, HuH-7, and PLC/PRF/5. Finally, we investigated HCC invasion, proliferation, and angiogenesis using K19-positive HCC specimens. Results Analysis of HCC surgical specimens revealed that K19-positive HCC exhibited higher invasiveness, metastatic potential, and poorer prognosis. In vitro experiments using the human HCC cell lines revealed thatK19 silencing suppressed cell growth by inducting apoptosis or upregulatingp16 andp27, resulting in cellular senescence. In addition, transfection withK19 siRNA upregulated E-cadherin gene expression, significantly inhibited the invasive capacity of the cells, downregulated angiogenesis-related molecules such asvasohibin-1 (VASH1 ) andfibroblast growth factor 1 (FGFR1 ), and upregulatedvasohibin-2 (VASH2 ). K19-positive HCC specimens exhibited a high MIB-1 labelling index, decreased E-cadherin expression, and high microvessel density around cancer foci. Conclusion K19 directly promotes cancer cell survival, invasion, and angiogenesis, resulting in HCC progression and poor clinical outcome. K19 may therefore be a novel drug target for the treatment of K19-positive HCC.